1997
DOI: 10.1093/hmg/6.7.1079
|View full text |Cite
|
Sign up to set email alerts
|

Translocation breakpoint maps 5 kb 3' from TWIST in a patient affected with Saethre-Chotzen syndrome

Abstract: Saethre-Chotzen syndrome, a common autosomal dominant craniosynostosis in humans, is characterized by brachydactyly, soft tissue syndactyly and facial dysmorphism including ptosis, facial asymmetry, and prominent ear crura. Previously, we identified a yeast artificial chromosome that encompassed the breakpoint of an apparently balanced t(6;7) (q16.2;p15.3) translocation associated with a mild form of Saethre-Chotzen syndrome. We now describe, at the DNA sequence level, the region on chromosome 7 affected by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 46 publications
1
43
0
Order By: Relevance
“…One can speculate that these patients carry short scale deletions flanking the TWIST gene and downregulating its expression via a positional effect, especially as a translocation deletion located 5 kb downstream from the TWIST gene has been recently described in association with mild ACS III. 26 Interestingly, such a positional effect has been previously reported for PAX 6 in aniridia, 27 GLI 3 for Greig syndrome 28 and SOX 9 for campomelic dysplasia. 29 Re-examination of clinical symptoms in our ACS III patients carrying TWIST mutations revealed that they consistently presented a ptosis with 2-3 syndactyly of the hands and abnormal ears (round and small with TWIST gene mutations in Saethre-Chotzen syndrome V El Ghouzzi et al t frequent crus helicis) regardless of the molecular subtype.…”
Section: Discussionmentioning
confidence: 74%
“…One can speculate that these patients carry short scale deletions flanking the TWIST gene and downregulating its expression via a positional effect, especially as a translocation deletion located 5 kb downstream from the TWIST gene has been recently described in association with mild ACS III. 26 Interestingly, such a positional effect has been previously reported for PAX 6 in aniridia, 27 GLI 3 for Greig syndrome 28 and SOX 9 for campomelic dysplasia. 29 Re-examination of clinical symptoms in our ACS III patients carrying TWIST mutations revealed that they consistently presented a ptosis with 2-3 syndactyly of the hands and abnormal ears (round and small with TWIST gene mutations in Saethre-Chotzen syndrome V El Ghouzzi et al t frequent crus helicis) regardless of the molecular subtype.…”
Section: Discussionmentioning
confidence: 74%
“…Alternatively, the translocations may cause deleterious changes in the expression of nearby genes by separating essential cis-acting regulatory elements from the transcription units. This kind of position effect has been described for many human disorders associated with balanced translocations, including SaethreChotzen syndrome (Krebs et al, 1997), Townes-Brocks syndrome (Marlin et al, 1999), and blepharophimosis/ptosis/epicanthus inversus syndrome (Crisponi et al, 2001), another disorder associated with POF. In each case the proposed position effect is on a gene that is either haploinsufficient or X-linked, and the effect was seen when decreased expression from one allele causes a phenotype (Kleinjan and van Heyningen, 1998).…”
Section: Discussionmentioning
confidence: 77%
“…At present it is unclear whether TWISTNB and HNATO3 (localised centromeric to TWIST) or HDAC9 and SNX13 (localised telomeric to TWIST) are the major genes responsible for the clinical feature of learning disability. Based on the data from translocation patients described by Krebs et al (1997) and Rose et al (1997) it is evident, that HDAC9 and SNX13 most likely can be excluded as candidate genes. All translocation breakpoints known so far occur telomeric from TWIST and by this dislocate HDAC9 and SNX13 or disrupt the HDAC9 gene region.…”
Section: Expression Of Twistnbmentioning
confidence: 99%